xalia
Answered

Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve for x: 3(x + 1) = −2(x − 1) − 4

1

−1

−5

−25


Sagot :

Answer:

x = - 1

Step-by-step explanation:

3(x + 1) = - 2(x - 1) - 4 ←  distribute parenthesis on both sides

3x + 3 = - 2x + 2 - 4

3x + 3 = - 2x - 2 ( add 2x to both sides )

5x + 3 = - 2 ( subtract 3 from both sides )

5x = - 5 ( divide both sides by 5 )

x = - 1